2014
DOI: 10.4209/aaqr.2013.03.0099
|View full text |Cite
|
Sign up to set email alerts
|

The Emission of Polychlorinated Dibenzo-p-dioxins and Polychlorinated Dibenzofurans from Steel and Cement-Kiln Plants in Vietnam

Abstract: Stack gas and fly ash samples were collected in two steel plants and three cement kiln plants for the determination of polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs). A standard sampling method (U.S EPA method 23) was used following the requirements for isokinetic sampling of stack gas emission. The quantification of PCDD/Fs was done by high resolution gas chromatography, coupled with high resolution mass spectrometry (HRGC/ HRMS). The results demonstrated that PCDD/F concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Lots of studies have indicated that the formation and emission of PCDD/Fs from the cement kiln is inevitable (Giannopoulos et al, 2007;Conesa et al, 2008;Karstensen, 2008). For instance, the I-TEQ values were in , while I-TEQ concentration varied from 0.033 to 0.837 ng TEQ Nm -3 in Vietnamese cement plant (Thuong et al, 2014). By using long-term sampling devices, levels of 0.009 ng I-TEQ Nm -3 were also detected in the flue gas of cement kilns (RiveraAustrui et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Lots of studies have indicated that the formation and emission of PCDD/Fs from the cement kiln is inevitable (Giannopoulos et al, 2007;Conesa et al, 2008;Karstensen, 2008). For instance, the I-TEQ values were in , while I-TEQ concentration varied from 0.033 to 0.837 ng TEQ Nm -3 in Vietnamese cement plant (Thuong et al, 2014). By using long-term sampling devices, levels of 0.009 ng I-TEQ Nm -3 were also detected in the flue gas of cement kilns (RiveraAustrui et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Production of iron and steel is an important source of air pollutants including particulate matter (PM). Previous studies identify iron and steel plants as a major contributor of PM and persistent organic pollutants to air in the vicinity of plants (Amodio et al, 2013;Thuong et al, 2014;Xiao et al, 2014). Atmospheric particulates have potentially adverse impacts on human health through inhalation and respiratory deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Combustion processes (Correa et al, 2006;Shih et al, 2006;Chiu et al, 2011) involving chlorine containing organic matter ) such as municipal solid waste incineration (Lee et al, 2003), laboratory waste incinerators (Liao et al, 2014;Wu et al, 2014), hazardous waste incinerators , iron ore sintering plants (Fang et al, 2011), steel and cement kilns (Van Thuong et al, 2014), landfill fires (Moussiopoulos et al, 2006), vehicle tailpipe exhausts (Chuang et al, 2010), boilers , fast food restaurants , coal fire-power plants (Lin et al, 2010b), bio-mass open burning (Shih et al, 2008;Chang et al, 2013;Chang et al, 2014) and dust storms (Chi et al, 2014) have been pointed out to be among the leading primary sources of PCDD/Fs and other dioxin like compounds. The emission of PCDD/Fs from the mentioned processes can be attributed to either their presence the feedstock, or be formed from chlorine containing precursors compounds as well as be formed through the de novo mechanism at certain temperature window Fujimori et al, 2014).…”
Section: Introductionmentioning
confidence: 99%